Students’ Perceptions of Using ChatGPT in Completing Academic Writing Tasks - Fatimah, Siti; Suryani, Suryani; M, Ugahara (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
The purpose of this research was to explore students’ perceptions of using ChatGPT in completing academic writing tasks. This research was descriptive research with qualitative approach. Data collection in this study were collected through semi-structured interview. Respondents for this research were five fourth-semester English education students at Abulyatama University who actively used ChatGPT in their writing process. The aspects examined in this research included the frequency of use, advantages and disadvantages of ChatGPT, writing improvements, and the need for peer and lecturer feedback. The results showed that students perceived ChatGPT as a beneficial tool in improving grammar, vocabulary, structure, and confidence in completing academic writing tasks. However, they also noted disadvantages such as overdependence, reduced critical thinking, and occasional inaccuracy. Students expressed that while ChatGPT supported their learning, human feedback remained essential. The findings indicate that ChatGPT can be effectively used as a supplementary tool for completing academic writing tasks when guided by responsible use and critical evaluation.